ECOTOURISM DEVELOPMENT OF ISLAMIC BASED - Darmadi, Yudi (Universitas Djuanda, 2016)
Real Work Lecture is one manifestation of Tri Dharma College namely community service.Real Work Lecture has a positive impact for the community, both in terms of development ofinfrastructure, economic development, education, religious and environmental hygiene. Inaddition, the Real Work Lecture is also has provided invaluable experience for students KKN2016 had engaged in service learning her in Kampung Cipicung village Kabandungandistricts Kabandungan Sukabumi, about how to live in the midst of society, how to socializewith people, to exchange thoughts with the public, and take on the life sciences communityto incorporate economic sciences of Islam to the local community that this Cipicung villagecan grow in terms of local and cultural potential. By raising the local knowledge and thevarious tourist attractions in sub Kabandungan.